ANALYSIS OF HUMAN RESOURCES COMPETENCE AND QUALITY OF LOGISTICS SERVICES ON CUSTOMER SATISFACTION THAT IMPACT ON EMPLOYEE PERFORMANCE AT PT. TIKI JALUR NUGRAHA EKAKURIR (JNE) BRANCH CIPUTAT - Marliana Budhiningtias Winanti; Tetet Cahyati (Politeknik APP Jakarta, 2021)
The aim of this study was to analyze the influence of HR competence and quality of logistics services on customer satisfaction which has an impact on employee performance at PT. Tiki Jalan Nugraha Ekakurir (JNE) Ciputat Branch, South Tangerang. In this study, a quantitative research type was used with a survey approach. The method used was simple random sampling, with a sample of 99 customers from PT. Tiki Jalan Nugraha Ekakurir (JNE) Ciputat Branch, South Tangerang. The data analysis technique of this study used PLS software version 3.0 (Partial Least Square) with the results obtained that (1) HR competence has no effect on customer satisfaction with at statistical value of 1.904 < t table of 1.984 and P-value 0.058 > 0.05.